2022
DOI: 10.1111/vde.13138
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, double‐blinded comparison between subcutaneous rush and intralympathic allergen immunotherapy induction in atopic dogs

Abstract: Background: Atopic dermatitis (AD) is one of the most common skin diseases in small animal practice. Allergen immunotherapy (AIT) is the only curative treatment for the disease, and oral, subcutaneous and intralymphatic administration of allergens are commonly employed. Objectives: To compare the efficacy of AIT following an induction phase with intralymphatic injections (ILIT) or rush immunotherapy (RIT). Animals: Fifty privately owned dogs with AD. Materials and Methods:In a double-blinded study, dogs were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 43 publications
(127 reference statements)
0
15
1
Order By: Relevance
“…However, other ILIT studies have shown improvement in clinical scores within three to six months. 25,26 Moreover, in the study by Mueller et al 27 significant improvement of total score (skin lesion, pruritus and medication scores) was already seen from one month of treatment.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…However, other ILIT studies have shown improvement in clinical scores within three to six months. 25,26 Moreover, in the study by Mueller et al 27 significant improvement of total score (skin lesion, pruritus and medication scores) was already seen from one month of treatment.…”
Section: Discussionmentioning
confidence: 91%
“…By contrast, most dogs treated with ILIT in previous studies were classified as having mild-to-moderate AD. [25][26][27] Another factor contributing to the lower efficacy rate also may be related to more stringent concurrent medication use in this study in combination with more severe disease. Just enough systemic medication was given to keep clinical signs ethically acceptable without the reduction of pVAS and CADESI values to normal levels (Figure S1).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations